2019
DOI: 10.12890/2019_001123
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Gallbladder

Abstract: Gallbladders have been reported in various ectopic locations. An intrahepatic gallbladder is one where the gallbladder lies within the liver parenchyma or has a subcapsular location along the anterior inferior right lobe of the liver. Intrahepatic gallbladders can have impaired function leading to the formation of gallbladder stones. We present the case of a 57-year-old man who was found to have an intrahepatic gallbladder which was not detected before a retrograde open cholecystectomy was carried out without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The intrahepatic location, the second commonest ectopic site, may impair the biliary drainage resulting in biliary stasis and cholelithiasis. 7 Ultrasonography is incapable of differentiating intrahepatic gallbladder duplications from mimicking lesions such as a Phrygian capped gallbladder, Todani type II choledochal cysts, 8 gallbladder diverticuli, cystic intraductal papillary neoplasms of the bile duct, and localized Caroli's disease. 9 The sensitivity of ultrasonography and CT in diagnosing duplicated gallbladders is similar at about 60%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intrahepatic location, the second commonest ectopic site, may impair the biliary drainage resulting in biliary stasis and cholelithiasis. 7 Ultrasonography is incapable of differentiating intrahepatic gallbladder duplications from mimicking lesions such as a Phrygian capped gallbladder, Todani type II choledochal cysts, 8 gallbladder diverticuli, cystic intraductal papillary neoplasms of the bile duct, and localized Caroli's disease. 9 The sensitivity of ultrasonography and CT in diagnosing duplicated gallbladders is similar at about 60%.…”
Section: Discussionmentioning
confidence: 99%
“…The intrahepatic location, the second commonest ectopic site, may impair the biliary drainage resulting in biliary stasis and cholelithiasis. 7 …”
Section: Discussionmentioning
confidence: 99%
“…4 Monib et al concluded that awareness of ectopic gallbladder allows proper preoperative planning and will often require surgery at the earliest due to increased risk of cholelithiasis. 5 Alkatout et al showed that the very rare entity of extra abdominal placed gallbladder in a neonate without the typical cholestasis symptoms. 6 Schultz et al did a report on accurate diagnosis of intrahepatic gallbladder with the help of 99mTc sulfur colloid and 131I-rose bengal in a cirrhotic patient with suspected intrahepatic neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The gallbladder is a small sac, which is found on the visceral side of the liver. The gallbladder is adherent to the posterior liver along one side (the gallbladder 'bed'), and in rare cases, is not visible as it can be entirely intrahepatic (3). A thorough inspection should be given in cases of biliary atresia with Kasai porto-enterostomy, because the gallbladder can be very small or absent (4).…”
Section: Introductionmentioning
confidence: 99%